2023
DOI: 10.1001/jamadermatol.2022.5850
|View full text |Cite
|
Sign up to set email alerts
|

Light-Related Cutaneous Symptoms of Erythropoietic Protoporphyria and Associations With Light Sensitivity Measurements

Abstract: ImportanceErythropoietic protoporphyria (EPP) is a rare and underdiagnosed genetic disease characterized by painful sensitivity to light. A better understanding and characterization of its light-induced cutaneous symptoms may aid in the identification of EPP in patients.ObjectivesTo describe the cutaneous symptoms of erythropoietic protoporphyria (EPP) and to determine if these symptoms are associated with the degree of light sensitivity.Design, Setting, and ParticipantsThis was a cross-sectional study of adol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 18 publications
1
1
0
Order By: Relevance
“…The most common symptoms reported were burning, pain, swelling, tingling, itching, sensitivity to touch, warmth/heat sensation, blisters, redness/discoloration, and sensitivity to hot/cold, which is consistent with previous studies. 1 , 3 Though burning and pain were reported as distinct symptoms by some participants, consistent with previous studies and case reports, 5 , 28 , 29 others reported “burning pain”. It is likely patients interpret these concepts on a continuum when describing their symptoms.…”
Section: Discussionsupporting
confidence: 89%
“…The most common symptoms reported were burning, pain, swelling, tingling, itching, sensitivity to touch, warmth/heat sensation, blisters, redness/discoloration, and sensitivity to hot/cold, which is consistent with previous studies. 1 , 3 Though burning and pain were reported as distinct symptoms by some participants, consistent with previous studies and case reports, 5 , 28 , 29 others reported “burning pain”. It is likely patients interpret these concepts on a continuum when describing their symptoms.…”
Section: Discussionsupporting
confidence: 89%
“…Short-time exposure to light causes severe pain (neuropathic pain) in children, which usually occurs 1–20 min after direct exposure to the sun and may last several days and be unresponsive to analgesics. The skin may become erythematous and oedematous, with the presence of petechiae and erosions [ 16 , 18 , 19 ]. Quality of life in patients suffering from EPP is severely affected since early childhood due to their light-avoiding behaviour and limitations in social interactions [ 20 ].…”
Section: Skin Diseases With the Use Of Afamelanotidementioning
confidence: 99%